Channels of vision and the poetics of drawing: Strategies for teaching. (July 2014) - Riley, Howard
This article introduces a novel approach to pedagogy within an art school in the UK HE sector, based upon a synthesis of perception theory and communication theory. It is argued that art students' drawing is empowered by strategies of teaching informed by aspects of James J. Gibson's ecological approach to visual perception relevant to an understanding of the variety of information contained in the structure of light. Three types of perceivable information are identified: the distal, the haptic, and the proximal, described as channels of vision, and illustrated with examples of the author's drawings. Aspects of Roman Jakobson's communication theory are introduced, and both theorists' insights are amalgamated in a systemic-functional semiotic matrix describing the domain of drawing derived from Michael Halliday's systemic-functional semiotic model for language. The matrix has informed the design of a curriculum for drawing, and a project from this curriculum is presented and illustrated with students' drawings.